Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga, dan Lokasi Terhadap Kepuasan Pelanggan Mie Gacoan Majapahit Semarang - Savero, Raihan Vito; Kurniawan, Rudi; Chasanah, Amalia Nur; Wibowo, Mochammad Eric Suryakencana (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to examine and analyze the effect of product quality, service quality, price and location on customer satisfaction at Mie Gacoan Majapahit Semarang. The dependent variable used in this study is Customer Satisfaction (Y) while the independent variables used are Product Quality (X₁), Service Quality (X2), Price (X3), and Location (X4). The sample in this study were 100 respondents. The sampling technique used purposive sampling. The analysis methods used are. multiple linear analysis, instrument test, classical assumption test, and hypothesis testing. From the results of the research conducted, it shows that service quality and location have a positive and significant effect on customer satisfaction. Product quality and price variables have no effect on customer satisfaction.